CORRELATION BETWEEN LIFE SATISFACTION AND HEART RATE VARIABILITY COHERENCE AMONG BLUE-COLLAR WORKERS – CASE STUDY IN A MALAYSIAN ELECTRONIC MANUFACTURING COMPANY - Sutarto, Auditya Purwandini; Khairai, Kamarulzaman bin Mahmad; Wahab, Muhammad Nubli Abdul; Sukadarin, Ezrin Hani (Lux Mensana: Journal of Scientific Health, 2023)
Introduction. In addition to having a higher risk of more physical and psychological health problems, blue-collar workers form the largest proportion of the workforce in industries. Thus, it is important to ensure their well-being which can have broader benefits for economic growth and society. This study aims at investigating the relationship between subjective well-being, namely life satisfaction and heart rate variability (HRV) coherence as an objective indicator. The second aim is to evaluate whether any differences in HRV coherence across three levels of life satisfaction groups (dissatisfied, neutral, and satisfied) after a brief session of resonant breathing training. Methods. A total of 313 female blue-collar workers from an electronic manufacturing company participated in this study. All participants completed a satisfaction with life scale (SWLS). Their HRV coherences were then recorded at baseline or rest and after attending a brief session of resonant breathing. Results and Analysis. We found a significant correlation between life satisfaction and HRV coherence after the intervention but not at rest, implying a current state of cardiac activity did not reflect workers’ attitudes toward their life. Moreover, less satisfied workers showed greater cardiac coherence improvement than those who perceived more satisfaction in life. Discussion. This finding suggests that brief resonant breathing training can help workers achieve greater HRV coherence which offers its potential as a strategy to combat workplace stressors.